Perpetration of Violence by Female Sex Workers in Papua New Guinea: ‘We will Crush their Bones’ - Kelly-Hanku, Angela (The British journal of criminology, 2021)
There is a small but important body of literature on female sex workers’ (FSWs) violence towards others, but little of that focused on low- and middle-income countries. Drawn from a larger biobehavioural study of FSWs in three cities in Papua New Guinea, we analyse the interviews from 19 FSWs who reported having perpetrated physical violence towards four major groups: (1) ex-husbands; (2) clients; (3) other sex workers and (4) other people (mainly women). Our study demonstrates that FSWs’ use of violence arises from a complex set of social, material and gendered circumstances and cannot be addressed in isolation from other aspects of their lives.